Incentives, ability and disutility of effort - Silvia Martinez-Gorricho; Miguel Sanchez Villalba (SERIEs - Journal of the Spanish Economic Association, 2021)
We generalize the disutility of effort function in the linear-Constant Absolute Risk Aversion (CARA) puremoral hazardmodel.We assume that agents are heterogeneous in ability. Each agent's ability is observable and treated as a parameter that indexes the disutility of effort associated with the task performed. In opposition to the literature (the "traditional" scenario), we find a new, "novel" scenario, in which a high-ability agent may be offered a weaker incentive contract than a low-ability one, but works harder. We characterize the conditions for the existence of these two scenarios: formally, the "traditional" ("novel") scenario occurs if and only if the marginal rate of substitution of the marginal disutility of effort function is increasing (decreasing) in effort when evaluated at the second-best effort. If, further, this condition holds for all parameter values and matching is endogenous, less (more) talented agents work for principals with riskier projects in equilibrium. This implies that the indirect and total effects of risk on incentives are negative under monotone assortative matching.
Keywords: C78; D03; D82; D86; 330; Incentives; Ability; Disutility of effort; Endogenous matching; Moralhazard